Sensor Fusion in Integrated Circuit Fault Diagnosis Using a Belief Function Model. (2008) - Zhu Zhu, Daqi Daqi; Gu Gu, Wei Wei
Abstract : In this paper, a multi-senor information fusion method based on the D-S (Dempster-Shafer) evidence theory is presented for fault diagnosis in an integrated circuit. By measuring the temperature and voltages of circuit components, the fault belief function assignment of two sensors to circuit components is calculated, and the fusion fault belief function assignment is obtained by using the D-S evidence theory. Then the actual fault component is precisely found according to the fusion data. Comparing the diagnosis results based on separate original data with the ones based on D-S theory fusion method, it is shown that the D-S information fusion fault diagnosis method is more accurate. Finally, two fault diagnosis examples of the simple signal magnification circuit and the integrated circuit of industrial case are given.